Infection biomarkers in primary care patients with acute respiratory tract infections–comparison of Procalcitonin and C-reactive protein. Issue 1 (December 2016) - Meili, Marc; Kutz, Alexander; Briel, Matthias; Christ-Crain, Mirjam; Bucher, Heiner; Mueller, Beat; Schuetz, Philipp
Abstract Background There is a lack of studies comparing the utility of C-reactive protein (CRP) with Procalcitonin (PCT) for the management of patients with acute respiratory tract infections (ARI) in primary care. Our aim was to study the correlation between these markers and to compare their predictive accuracy in regard to clinical outcome prediction. Methods This is a secondary analysis using clinical and biomarker data of 458 primary care patients with pneumonic and non-pneumonic ARI. We used correlation statistics (spearman's rank test) and multivariable regression models to assess association of markers with adverse outcome, namely days with restricted activities and persistence of discomfort from infection at day 14. Results At baseline, CRP and PCT did not correlate well in the overall population (r2  = 0.16) and particularly in the subgroup of patients with non-pneumonic ARI (r2  = 0.08). Low correlation of biomarkers were also found when comparing cut-off ranges, day seven levels or changes from baseline to day seven. High baseline levels of CRP (>100 mg/dL, regression coefficient 1.6, 95 % CI 0.5 to 2.6, sociodemographic-adjusted model) as well as PCT (>0.5ug/L regression coefficient 2.0, 95 % CI 0.0 to 4.0, sociodemographic-adjusted model) were significantly associated with larger number of days with restricted activities. There were no associations of either biomarker with persistence of discomfort at day 14. Conclusions CRP and PCT levels do not well correlate, but both have moderate prognostic accuracy in primary care patients with ARI to predict clinical outcomes. The low correlation between the two biomarkers calls for interventional research comparing these markers head to head in regard to their ability to guide antibiotic decisions. Trial registration Current Controlled Trials, ISRCTN73182671